Color and flavor development of roasted jackfruit (Artocarpus hetrophyllus L.) seeds - Azeez, Shakirah Omotoke (2015)
Jackfruit (Artocarpus hetrophyllus) seed is known to be an underutilized seed. It has many potentials and applications in food, cosmetics, pharmaceuticals and bionanotechnology industries. Most studies on jackfruit seed (JFS) have been focused on the chemical, functional, and nutritive values of both raw and processed (cooked) jackfruit seed flour. The increasing demand for under-utilized seeds as alternative cheap source of nutritious food snack is making JFS gain more attention in the recent years. The aim of this research therefore was to investigate the flavor and color development in JFS during roasting, through; chemical analysis, sugar profiling and amino acid profiling of both raw and roasted JFS; color development analysis using response surface methodology (RSM); effect of roasting condition on the structural changes of the starch granules using scanning electron microscopy (SEM) and Fourier Transform Infrared spectroscopy (FTIR); and lastly flavor development analysis using gas chromatography-olfactometry (GC-O) and gas chromatography-mass spectrometry (GC-MS) coupled with aroma extract dilution analysis (AEDA) for the identification of key odorants. For chemical analysis of the three cultivars of jackfruit seed analyzed,results showed that the starchy seeds were very high in moisture (53.16-62.41%) and starch (15.95-32.04%), moderately high in protein (7.62-8.46%), dietary fiber (2.80-7.19%), ash content (3.19-3.70%), but low in fat (1.09-1.48%). Analyses of the color and flavor precursors (amino acids, sugar and fatty acids) of JFS cultivars showed that cultivar J31 had the highest contents of amino acids such as methionine, leucine, alanine and threonine. Fatty acids linoleic and linolenic were also the highest. Although, the sugar contents were low, fructose and sucrose were significantly higher in cultivar J31. The effect of roasting conditions on the color development (L*, a*, b* and browning intensity) and fracturability (measured using Universal Texture Analyzer) using a three factor central composite rotatable design (CCRD) gave R square of 0.81, 0.96, 0.93, 0.92, and 0.74, respectively. The optimum roasting conditions were found to be at temperature of 153.4 oC, time 34.4 minutes, pH 6.34 and a composite desirability of 0.95. The micro-structural studies of both raw and roasted JFS at different roasting levels showed a B-type category of starch granules with semioval to round/bell shapes (5-9μm in diameter), which became flattened as the roasting temperature and time increased. The IR spectra was in the 4000-1000 cm-1 region and it was described by five main modes; O-H, C-H stretching, C=C, C-H bending and C-O. The major functional group with the highest intensity in both raw and roasted JFS was the C-O bond stretch of esters. A total of 95 compounds were identified using the gas chromatography-olfactometry (GC-O) on a diphenyl dimethyl polysiloxane (DB-5) and free fatty acid phase (FFAP) columns. The major classes of aroma compounds include aldehyde, esters, alcohols, alkanes, monoterpenes and ketones. Application of aroma extract dilution analysis (AEDA) to the flavor extract from both raw and roasted JFS revealed 16 and 26 odor-active compounds respectively in the flavor dilution (FD) range of 16-32. Aromas perceived on the GC-O were dominated by Flowery, green,pungent-sulforous, and sweet-caramel and woody aromas, which were more persistent in the roasted seed. Roasted jackfruit seeds can be used as an alternative healthy snack product due to its good source of dietary nutrients. Also, the most needed literature on the optimum roasting conditions for color and flavor development can be exploited by researchers and food industries at large.